Effect of different levels of sharpness processing filter on the measurement accuracy of endodontic file length - Nastaran Farhadi; Ali Shokraneh; Masoud Saatchi (Wolters Kluwer Medknow Publications, 2016)
Introduction: The present study was undertaken to evaluate the effect of different levels of sharpness processing filter on the accuracy of endodontic file length determination using digital periapical radiography. Materials and Methods: Forty human single-rooted permanent teeth were selected and International Organization for Standardization (ISO) #08 K-files were inserted into the root canals of the teeth. The file lengths were measured with a digital caliper as the gold standard. Digital periapical images were obtained using a phosphor storage plate as a detector. Three levels of sharpness tool of Scanora software program version 5.1 was used to produce enhanced images: Sharpen 1 (mild level), Sharpen 2 (moderate level), and Sharpen 3 (high level). Two radiologists and two endodontists measured file lengths on the original and enhanced images. The measurements were compared using repeated measures ANOVA and Bonferroni tests (α = 0.05). Results: There were no significant differences between the measurement accuracy of original images and that of the Sharpen 1 and Sharpen 2 enhanced images (P > 0.05). However, significant differences were found between the measurement accuracy of original and that of the Sharpen 3 enhanced images (P < 0.05). In addition, there were no significant differences among enhanced images processed by different levels of sharpness processing filter (P > 0.05). Conclusion: The application of mild and moderate levels of sharpness processing filter did not influence the accuracy of endodontic file length determination. However, high-level sharpness processing filter is not recommended due to its unfavorable effects on measurement accuracy.